If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15x-40=8x-23
We move all terms to the left:
-15x-40-(8x-23)=0
We get rid of parentheses
-15x-8x+23-40=0
We add all the numbers together, and all the variables
-23x-17=0
We move all terms containing x to the left, all other terms to the right
-23x=17
x=17/-23
x=-17/23
| X2+5x=50 | | x^2-5x+0.5=0 | | 2(1+2x)=9x-3 | | 5r+6=11r | | 1/0(x+50)=-3x-13+4x | | 3x-2(-13/2-3x/2)=13 | | 3(2x+5)-10=47 | | 2u+1=u+12 | | 4x+5=-4x+7 | | 6.7=y-3.4 | | 3(-2-v)=5v-6 | | 4-(x+4)=3-8 | | x+25+125=180 | | 2(4x-11)=5x-10 | | |2x-25|=|3x+5| | | -3m+2=2m+7 | | 3/2v-2=-1/5v-4/5 | | 8k+7-7k=48 | | 7-5m+6m-1=4m | | 1/10(x+50)=-3-13+4x | | (1-y)/3=2/5 | | 4(2x-4)=6x-10 | | 2-8n+6n=42 | | 15n3=15 | | 4.4x-11.9=23.3 | | –6−3x=–2x | | 7x2+2x-2=0 | | 17x-50=7x | | -4(-3x+2)=16 | | -2=7x-5x-6 | | –6−3n=–2n | | 4.5x-8.6=18.4 |